Transcendence and film cinematic encounters with the real - Nichols, David P. (David Paul) (Lexington Books, 2019)
In this book, ten experts in philosophy of film explore the importance of transcendence for cinema as an art form in the films of the great directors, David Cronenberg, Karl Theodor Dreyer, Federico Fellini, Werner Herzog, Stanley Kubrick, David Lynch, Terrence Malick, Yasujiro Ozu, and Martin Scorsese.